Systematic review and meta-analysis of animal listeriosis in Ethiopia - Sagni Diba; Habtamu Terefe (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Listeriosis is a widespread zoonotic disease that becomes an important source of food borne infections all over the world. Mostly it affects cattle herd, sheep and goat flocks. The objective of the research was to estimate prevalence of Listeriosis in Ethiopia and to provide the distribution of the disease at national level. The meta-analysis was conducted to collect the information and to provide a pooled prevalence estimate at national level and identify potential predictors. The secondary data were searched from Published research and review written by English language during the period between October, 2000 and June 2018. The publications were selected based on inclusive and exclusion criteria for data extraction and analysis by Meta-Analysis Software Relevant animal level data on 1460 was collected from 14 published manuscripts and one master's thesis resulting conformed to predefined criteria. The dataset was analyzed using a meta-analytical technique. The pooled prevalence assessed computed for listeriosis problem was 23.9% with confidence interval of 17.6, 30.2. Among the predictors considered for heterogeneity analysis only sample size and listeriosis the prevalence was showed to decrease with increasing sample size. This study showed occurrence of animal listeriosis at national level. Thus, approach used to know the prevalence of the disease at national level.